'In order that they may attain ease, confidence, and comfort': myth and history in Moana Roa (1951) and Drums Across the Lagoon (1960). Issue 3 (1st September 2016) - Sigley, Simon
ABSTRACT: Moana Roa (1951) and Drums Across the Lagoon (1960) are examples of prestige propaganda, documentary films that give cinematic voice to significant post-WWII changes in the way New Zealand administered the Cook Islands, annexed to New Zealand in 1901 by the UK. From documenting successive government efforts to conform to United Nations declarations on decolonisation, to constructing mythic cinematic fictions that articulate Eurocentric concepts of 'noble savages' and 'dusky maidens' living a life of ease in prelapsarian spaces, these films document material change and construct the symbolic role that the South Pacific has played in the cultural imaginary of western nations.